SUMBER DAYA PENDIDIKAN DI ERA ARTIFICIAL INTELLIGENCE: ANTARA PELUANG DAN TANTANGAN - Ahmad Buchori Muslim; Ahmad Aziz Faozi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Education in the era of Artificial Intelligence (AI) is a very important concern to prepare human resources (HR) owned by educational institutions in the face of rapid and dynamic changes in the world of work. Artificial Intelligence which is a technology that is increasingly developing and used in various sectors, including education. Education must adapt to the development of Artificial Intelligence technology and utilize it to improve the quality of learning. The purpose of this study is to analyze education in the era of Artificial Intelligence whether it can improve the quality of human resources as opportunities or replace them as challenges. The research method used in this research is a literature review by conducting a content analysis of a number of sources collected. The results showed that Artificial Intelligence technology can help in optimizing learning carried out in educational institutions. Skills in creativity, empathy, communication, and problem solving are still very important in creating effective and enjoyable learning experiences for students. Even so, the existence of human resources in the field of education remains indispensable in the era of Artificial Intelligence.